2005
DOI: 10.5194/acp-5-693-2005
|View full text |Cite
|
Sign up to set email alerts
|

A re-evaluation of the ClO/Cl<sub>2</sub>O<sub>2</sub> equilibrium constant based on stratospheric in-situ observations

Abstract: Abstract. In-situ measurements of ClO and its dimer carried out during the SOLVE II/VINTERSOL-EUPLEX and ENVISAT Validation campaigns in the Arctic winter 2003 suggest that the thermal equilibrium between the dimer formation and dissociation is shifted significantly towards the monomer compared to the current JPL 2002 recommendation. Detailed analysis of observations made in thermal equilibrium allowed to re-evaluate the magnitude and temperature dependence of the equilibrium constant. A fit of the JPL format … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
59
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 31 publications
13
59
2
Order By: Relevance
“…And because spectrum peak cross section are not determined independently in that study, chances are that the peak cross sections would also be erroneous. Using the different spectral shape as an argument against scaling to some other absolute cross sections, we do note that the von Hobe et al (2009) spectrum scaled to Lien et al (2009) also does not fully agree with the cross sections at longer wavelength proposed by the same group from Taiwan Jin et al, 2010). However, the molecular beam cross section measurements represent independent experiments at five different wavelengths, and they represent photolysis rather than absorption cross sections.…”
Section: O Sumińska-ebersoldt Et Al: Cloocl Photolysis At High Solamentioning
confidence: 94%
See 4 more Smart Citations
“…And because spectrum peak cross section are not determined independently in that study, chances are that the peak cross sections would also be erroneous. Using the different spectral shape as an argument against scaling to some other absolute cross sections, we do note that the von Hobe et al (2009) spectrum scaled to Lien et al (2009) also does not fully agree with the cross sections at longer wavelength proposed by the same group from Taiwan Jin et al, 2010). However, the molecular beam cross section measurements represent independent experiments at five different wavelengths, and they represent photolysis rather than absorption cross sections.…”
Section: O Sumińska-ebersoldt Et Al: Cloocl Photolysis At High Solamentioning
confidence: 94%
“…The two spectra have slightly different shapes but yield similar atmospheric J ClOOCl values. The results presented by Burkholder et al (1990) generally produced the best agreement in a number of studies comparing modelled and observed ClO x partitioning (Stimpfle et al, 2004;von Hobe et al, 2007;Schofield et al, 2008;Kremser et al, 2011) as well as ozone loss (Santee et al, 2003;Chipperfield et al, 2005;Frieler et al, 2006;Tripathi et al, 2006;von Hobe et al, 2007). Results of Papanastasiou et al (2009) are recommended in JPL 2011 (Sander et al, 2011).…”
Section: Investigated σ Clooclmentioning
confidence: 96%
See 3 more Smart Citations